Parents' perception of treatment-related toxicity in children treated according to the NOPHO ALL2008 protocol for acute lymphoblastic leukemia - Mogensen, Nina; Kreicbergs, Ulrika; Albertsen, Birgitte K.; Lähteenmäki, Päivi M.; Heyman, Mats; Harila, Arja (John-Wiley & Sons, 2025)
This study aimed to assess how parents perceived treatment-related side effects during acute lymphoblastic leukemia (ALL) treatment. Parents of children 1-17.9 years at diagnosis in Sweden, Finland, and Denmark who were alive and in first remission ≥6 months after end of ALL treatment were asked to respond on specific items regarding how their child was affected by side effects related to vincristine (VCR), corticosteroids, peg-asparaginase (ASP), and maintenance therapy, as well as overall impact of these treatments, complications in general, and their perception of impact on their child in comparison with other children with ALL. Parents of 307 children responded. More than a third reported that their child had been affected to a high extent by VCR (39.7%) and corticosteroids (35.8%), with walking difficulties, muscular weakness, pain, changes in appetite, and mood swings as the most common and severe symptoms. Reporting of these toxicities was lacking from the NOPHO ALL2008 database, except for peripheral paralysis (12.1%). For distinct toxicities reported in the NOPHO ALL2008 database, for example, thrombosis and pancreatitis, parent reports were similar to the database. Although a high overall negative impact during treatment was reported, parents generally rated the impact on their child as less, or similar, to other children with ALL. Parents perceived VCR and corticosteroid therapy, in particular, to have a negative impact on their child during ALL treatment, which was not captured in the NOPHO ALL2008 toxicity reporting. Our results highlight the importance of including patient/parent-reported outcomes in toxicity reporting.